Use of speckle tracking echocardiography in evaluating cardiac dysfunction in patients with acromegaly: an update - Huang, Rong; Jin, Jiewen; Zhang, Pengyuan; Yan, Kemin; Zhang, Hanrong; Chen, Xin; He, Wei; Guan, Hongyu; Liao, Zhihong; Xiao, Haipeng; Li, Yanbing; Li, Hai (Frontiers in Endocrinology, 2023)
In recent years, cardiovascular disease has garnered increasing attention as the second leading cause of death in individuals with acromegaly, following malignancy.Identifying cardiac dysfunction early in acromegaly patients for timely intervention has become a focal point of clinical research. Speckle tracking echocardiography, a wellestablished ultrasound technique, surpasses conventional Doppler ultrasound in its sensitivity to assess both local and global cardiac mechanics. It can accurately detect subclinical and clinical myocardial dysfunction, including myocardial ischemia, ventricular hypertrophy, and valvular changes. Over the past five years, the use of speckle tracking echocardiography in acromegaly patients has emerged as a novel approach. Throughout the cardiac cycle, speckle tracking echocardiography offers a sensitive evaluation of the global and regional myocardial condition by quantifying the motion of myocardial fibres in distinct segments. It achieves this independently of variations in ultrasound angle and distance, effectively simulating the deformation of individual ventricles across different spatial planes. This approach provides a more accurate description of changes in cardiac strain parameters. Importantly, even in the subclinical stage when ejection fraction remains normal, the strain parameters assessed by speckle tracking echocardiography hold a good predictive value for the risk of cardiovascular death and hospitalization in acromegaly patients with concomitant cardiovascular disease. This information aids in determining the optimal timing for interventional therapy, offering important insights for cardiac risk stratification and prognosis. In the present study, we comprehensively reviewed the research progress of speckle tracking echocardiography in evaluating of cardiac dysfunction in acromegaly patients, to pave the way for early diagnosis of acromegaly cardiomyopathy.